Maxims of Mike Lawford’s Utterances in Pay the Ghost Movie - Teofanne Nurinik Wea; Barli Bram (Politeknik Negeri Padang, 2022)
Expressing what we want or feel to others can be done directly and indirectly. But often, in some conversations, people fail to use directness. For communication to flow smoothly, maxims are utilized in discourse. On the other hand, people frequently fail to respect the maxim to convey implicit meaning, known as maxim flouting. This paper aimed to determine which maxims were performed by the main character Mike Lawford in the movie Pay the Ghost. The researchers used a descriptive qualitative approach to analyze the data. The researchers obtained the data by downloading and watching the film in the past. This study showed that the main character in this movie fulfilled 59 maxims consisting of 20 times using the maxim of relation, the maxim of quality 18 times, the maxim of manner 16 times, and the maxim of quantity five times. So, here the main character in this movie mostly used the maxim or relation in his conversation, and he rarely used the maxim of quantity. The main character also flouted 41 maxims which consisted of the maxim of quantity 20 times, the maxim of manner nine times, the maxim of quality seven times, and the maxim of relation five times. The main character in this movie mainly floated the maxim of quantity in his conversation.